2012
DOI: 10.1134/s1022795412050134
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of tacrolimus on human lymphocyte cells

Abstract: We designed in vitro study to determine possible genotoxic effects of tacrolimus (FK 506), which is used as a potent immunosuppressive drug, by using sister chromatid exchange (SCEs), chromosome aber ration (CAs), micronuclei tests (MN) and cell growth kinetics such as mitotic index (MI) and replication index (RI) in human lymphocytes. The ceils were treated with 5, 25, 50, and 100 ng/ml concentrations of tac rolimus, for 24 and 48 h treatment periods. Tacrolimus induced CA and MN frequency at all concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…4) reinforced these data. Our data obtained with FK-506 also corroborated those of Kurtoglu and Yuksel (2012) that did not find decrease of NDI in lymphocytes treated with concentrations of 5, 25 and 50 ng/ml of FK-506. These authors observed a decrease of the NDI in cells treated with the concentration of 100 ng/ml, that is extremely high and not observed clinically.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…4) reinforced these data. Our data obtained with FK-506 also corroborated those of Kurtoglu and Yuksel (2012) that did not find decrease of NDI in lymphocytes treated with concentrations of 5, 25 and 50 ng/ml of FK-506. These authors observed a decrease of the NDI in cells treated with the concentration of 100 ng/ml, that is extremely high and not observed clinically.…”
Section: Discussionsupporting
confidence: 95%
“…Mutagenic effect of FK-506 was demonstrated in cultures of human lymphocytes by Kurtoglu and Yuksel (2012) in concentrations ranging from 5 to 100 ng/ml and by Oliveira et al (2004) in concentrations ranging from 5 to 40 ng/ml. However, MRC-5 cells seems to be less sensitive to FK-506 since in our study mutagenic effects were observed only in concentrations higher than 24 ng/ml.…”
Section: Discussionmentioning
confidence: 96%
“…Genotoxic effects were reported with immunosuppressive drugs. Tacrolimus (FK-506), a potent immunosuppressive drug, induced chromosomal aberrations (CA) and MN frequency at all concentrations for 24 and 48 h (Kurtoglu and Yuksel 2012). Similar results were reported by others (Oliveira et al 2004), who found that cultures supplemented with the immunosuppressive drugs mycophenolate mofetil and tacrolimus showed higher amounts of micronuclei compared to controls in all concentrations tested.…”
Section: Discussionsupporting
confidence: 85%
“…Genotoxic substances induce damage in cells through interaction with the DNA and can result, including single-and double-strand breaks, cross-links between DNA bases and proteins, and chemical additions to the DNA. The occurrence of genomic damage, if left unrepaired, may result in the formation of DNA adducts, chromosome/chromatid breaks, or aneuploidy and is associated with the formation of micronucleus (MN), sister chromatid exchange (SCE), and overall genomic instability [17,26]. This may be the reason for SCE and MN formation in lymphocyte cells after CP treatment.…”
Section: Discussionmentioning
confidence: 99%